PHYSIOLOGICAL VARIABLES IN ANTHURIUM CULTIVATED UNDER DIFFERENT SHADING SCREEN - LIMA, Juliana Domingues; NOMURA, Edson Shigueaki; FUZITANI, Eduardo Jun; MODENESE-GORLA DA SILVA, Silvia Helena (Scientia Agraria, 2010)
Change in the spectral quality radiation can have significant effect on the growth and development of a crop plant. The objective of the present research was to evaluate the growth and yield of Anthurium andraeanum cv. Apalai under different shading screens. For developing such research, micropopageted seedlings were planted in beds under four screens (blue, red, black and thermo-reflective) with 70% of shading. The experimental design was in complete block randomized, with four treatments and four repetitions. The evaluations were carried out when the inflorescences presented standard for marketing. Higher values of leaf area were observed in plants grown under screen black, followed by plants grown under thermo-reflective screen, red screen, and finally, blue. Differences in specific leaf area and in the ratio of chlorophyll a/chlorophyll b were no significant between treatments. Chlorophylls content, maximum fluorescence (Fm) and the ratio of variable to maximum fluorescence (Fv/Fm) were low under blue and red screen, while the initial fluorescence (Fo) was high. The chlorophyll content correlated positively with Fv/Fm (r 0,96; R2 0,95; P < 0,0001). The black screen provided the best condition for growth.